MENGGAGAS PERAN DAN HUBUNGAN BIMBINGAN KONSELING DENGAN SEKOLAH: SYSTEMATIC LITERATURE REVIEW - Pardi Pardi; Aip Badrujaman (Jurnal Mahasiswa BK An-Nur : Berbeda, Bermakna, Mulia, 2024)
This research aims to identify the challenges faced in implementing Guidance and Counseling (GC) services in Indonesia and to explain 15 misconceptions held by students regarding the role of GC. Despite the important role GC plays in helping students develop their potential and plan for the future, challenges such as inadequate facilities, low collaboration among teachers, and a limited understanding of GC functions remain obstacles. This study utilizes qualitative data analysis with a systematic literature review approach to examine these issues. The findings indicate that, in addition to facility limitations, there is a need to enhance the competencies of GC teachers, intensify teacher collaboration, and increase the socialization of the GC role in schools. Moreover, the active involvement of school principals is deemed essential to improve the effectiveness of GC services. The research concludes that improving facilities, enhancing GC teacher competencies, strengthening teacher collaboration, and gaining support from the school administration are necessary for GC services to contribute optimally to students' development. Recommendations from this study include continuous training for GC teachers and increased efforts to raise awareness about the role of GC in schools across Indonesia.